Minimizing Air Traffic Disruption from Uncontrolled Space Debris Reentries - Irina Beatrice Stefanescu; Cristian Emil Constantinescu; Octavian Thor Pleter (Engineering Proceedings)
Uncontrolled space debris reentries pose a significant challenge to air traffic management (ATM), often requiring widespread airspace closures to mitigate the perceived risks to aviation safety. In a previous study, we established the probability of collision during such events to be in the order of 10−7 and classified the event as “extremely remote” but requiring mitigation action. Analyzing the temporal dynamics, we concluded that any given location remains at risk for no more than one minute. Building on these findings, this paper will investigate advanced mitigation strategies to reduce the operational impact of such reentries. We propose utilizing dynamic airspace allocation techniques, using information derived by enhanced reentry prediction models and real-time tracking. Transforming the spatial problem of airspace closures into a temporal one, the study demonstrates the feasibility of confining closures to dynamically moving zones with minimal disruption. A simulation for the Long March 5B reentry case study illustrates the potential for such measures to improve efficiency while maintaining safety standards.